PRAKTIK MURABAHAH PADA KANINDO SYARIAH - Shidarta, Eka Ananta; Astuti, Yuli Widi; Kholilah, Kholilah; Putri, Sheila Febriani (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2019)
Murabahah is 99.80% of the contracts used in financing distribution in Kanindo Sharia. This study aims to determine the problems faced by kanindo sharia in the implementation of the murabahah contract. This study uses phenomenology to answer the research objectives. Understanding of AO, guarantees, understanding of members, and accuracy of contracts used are four problems found in financing activities. The solutions used to solve these problems are training employees, rescheduling installments and withdrawing collateral, socializing and intensive approaches to members, as well as reviewing financing agreements. Accounting practices carried out by Kanindo Syariah are not in accordance with PSAK 102. Accounting recognition in accordance with PSAK 102 is only found in murabahah asset acquisition transactions.Â